Colonization of benthic invertebrates on artificial and natural substrate in a Neotropical lotic environment in Southern Brazil - Camargo, Nilce Svarcz Jungles de; Lehun, Atsler Luana; Rosa, Jonathan; Bueno-Krawczyk, Ana Carolina de Deus (Acta Scientiarum. Biological Sciences, 2019)
The objective of this research was to validate the colonization aniani4d process on natural and artificial substrates by benthic invertebrates in a tropical stream in South Brazil. The samples were performed in July and August-2012, and 32 samplers were used, being 16 natural and 16 artificial substrates. In each sample, two replicas were taken for each substrate at the 2th, 4th, 7th, 14th, 21th 28th, 35th and 42th days of colonization. The organisms were identified to the lowest possible taxonomic level. In both substrates 3,070 benthic invertebrates were detected, of which 1,753 individuals were collected on the natural substrate, and 1,317 on the artificial substrate. From the identified taxa 8.5% were not dominant (Anacroneuria, Orthocladiinae, Tupiara, Smicridea, Baetodes, Tupiperla, Macrogynoplax, Gripopteryx, Cylloepus, Macrelmis, Microcylloepus, Hetaerina, Argia, Coryphaeschna, Atopsyche, Pomacea, Corydalus, Leptohyphes and Eccoptura), and 31.5% were dominant (Tanypodinae, Chironominae, and Paragripopteryx). The genus Simulium was very common, dominant and abundant, representing 65% of the collected individuals. No significant difference was found in the abundance and species composition between artificial and natural substrates. On the natural substrate, the higher colonization index was at the 35th day with 459 individuals, and the lowest was at the 14th day, with 87. On the artificial substrate the highest index was at the 42th day with 337 individuals, and the lowest was at the 4th day, with 85. Both natural and artificial substrates are efficient in characterizing the benthic community. In the evaluation of the ecological succession, it was not possible to observe a pattern that described the process, since the composition was nearly constant throughout the study period.